Lossless and lossy modeling of ultrasonic imaging system for immersion applications: Simulation and experimentation. (October 2018) - Tarpara, Eaglekumar G.; Patankar, V.H.
Abstract: The design, modeling, optimization, and development of the entire ultrasonic imaging system is a complex task which involves an understanding of acoustic physics of transducer, acoustic properties of propagating medium, transmission cables and analog front-end electronics for generating and receiving of ultrasonic signals. Such immersion systems are extensively utilized in non-destructive testing (NDT) application for flaw detection, dimensional measurements, material characterization and many more. This paper presents the one-dimensional simulation modeling of the entire ultrasonic imaging system. For validation purpose, a single channel real-time ultrasonic imaging system has been designed and developed for laboratory application which contains high voltage ultrasonic spike pulser, high voltage protection circuits, ultrasonic receiver amplifiers, co-axial cables and an ultrasonic transducer. Lossless and lossy (low-loss) simulations have been performed for ultrasonic transducer and propagation medium using the transmission line model. Effects of non-ideal, frequency-dependent and non-linear components in high voltage excitation circuit (pulser), the receiver circuit and the effects of cables are also considered for modeling and simulation. Validation results of the entire ultrasonic imaging system provide very close agreement with lossy simulated results.